A process view of the role of integrated marketing communications during brand crises. Issue 3 (10th June 2019) - Hewett, Kelly; Lemon, Laura L.
Abstract : Purpose: This paper aims to explore the internal processes that can enable firms to identify and effectively respond to brand crises, with various groups coordinating and cooperating with each other, and also propose a guiding framework relevant for both managers and researchers. Design/methodology/approach: A grounded theory methodology was adopted. Data collection included open-ended interviews with 13 executives representing the integrated marketing communications (IMC) function, the integrated corporate communications function and external agencies supporting firms while navigating crises. Findings: Results revealed a three-stage process of internal coordination efforts during crises: sensing or scanning the environment and gathering insights regarding crises, informing or disseminating these insights throughout the organization to create transparency and responding or reacting to the event via a coordinated effort. Research limitations/implications: The framework does not directly incorporate input from consumers or customer contact employees, both of which may be relevant. Practical implications: Findings offer direction for managers to establish processes that prepare for and potentially reduce crises' negative consequences. In addition, this study reveals the importance of decision-makers being vigilant regarding social media's influence on such a process. Originality/value: The conceptual framework moves beyond previous brand crisis research, provides insight into the processes firms use to successfully manage crises and reveals the relevant factors related to internal coordination.